EFEKTIVITAS PENERAPAN ABSENSI BERBASIS APLIKASI “EBUDDY” DALAM MENUNJANG DISIPLIN KERJA APARATUR SIPIL NEGARA (STUDI KASUS SEKRETARIAT DPRD KAB. SIDOARJO) - Syauqi, M. Zidan; Prastyawan, Agus (Jurnal Inovasi Administrasi Negara Terapan, 2024)
The use of attendance through the E-Buddy application is used to see the impact of employee attendance discipline at the secretariat of provincial legislatives council Sidoarjo. The use of this attendance model has a problem, namely server downtime often occurs when used together, considering that this application is used simultaneously for a period starting from 07.20-07.30 WIB. This server down occurred because at that hour all OPD employees in Sidoarjo Regency on average carried out presence activities simultaneously. The impact of this server down can result in employees not being able to take attendance so that it is vulnerable to delays in employee attendance. The solution to this problem is that all employees are encouraged to carry out attendance activities before peak user hours so that there is no server buildup. The problem that the next researcher found was the application of sanctions related to Government Regulation No. 94 of 2021 regarding the discipline of civil servants, namely the problem of employees who were absent for a certain period of time were not immediately given sanctions in accordance with applicable regulations but coaching was carried out for the employees concerned. This study aims to determine the effectiveness and impact of using E-Buddy application-based attendance at the secretariat of provincial legislatives council Sidoarjo. The E- Buddy application is an application to support the performance of employees in Sidoarjo district and is run massively by Sidoarjo district government organizations. One of the features in the E- Buddy application is digital attendance by displaying facial photo evidence when entering and leaving, and Geotagging which is 200 meters from the work location. This study uses a qualitative method. The technique used in data collection is purposive sampling and data analysis techniques using data reduction, data display, and conclusion drawing. The results of this study resulted in 2 main discussions, namely the effectiveness and impact of using E-Buddy application-based attendance at the secretariat of provincial legislatives council Sidoarjo. Attendance Administration using E-Buddy at the secretariat of provincial legislatives council Sidoarjo is effective in supporting employee discipline because there has been an increase in the quality and quality of employees after using attendance via E-Buddy. The application of E- Buddy application-based attendance has an impact on employees, namely employees can have the responsibility to be present on time and complete their duties as state officials.   Keywords: Effectiveness, Discipline, E-Buddy, State Civil Apparatus